Introducing translation studies : - Munday, Jeremy (Routledge, 2012)
This introductory textbook provides an accessible overview of the key contributions to translation theory. Jeremy Munday explores each theory chapter-by-chapter and tests the different approaches by applying them to texts. The texts discussed are taken from a broad range of languages – English, French, German, Spanish, Italian, Punjabi, Portuguese and English translations are provided. A wide variety of text types are analyzed, including a tourist brochure, a children's cookery book, a Harry Potter novel, the Bible, literary reviews and translators' prefaces, film translation, a technical text and a European Parliament speech.